Determinants of Perceived Vulnerability to Illness among Coastal Communities in Mangrove Ecosystems - Thalita Aldila Pramitasari; Maria Theresia Sri Budiastuti; Sutarno Sutarno (Media Publikasi Cendekia Indonesia, 2026)
Coastal communities living in mangrove ecosystems are exposed to various environmental and health risks that may influence their perceived vulnerability to illness. Understanding the determinants of perceived vulnerability is important for improving community health resilience. Objective: This study aimed to identify the determinants of perceived vulnerability to illness among communities living in mangrove ecosystems. An observational cross-sectional study was conducted involving 67 residents of the Baros Mangrove Ecosystem, Bantul, Yogyakarta, who were recruited consecutively. Data were collected using a structured questionnaire measuring perceived environmental health, mangrove knowledge, community participation in mangrove management, and formal education, with gender treated as a covariate. Descriptive statistics, bivariate analysis, and multiple linear regression were used to analyze the data. Perceived vulnerability to illness was significantly and negatively associated with perceived environmental health (β = −1.112, p = 0.001), mangrove knowledge (β = −0.106, p = 0.032), and formal education (β = −0.106, p = 0.004). Community participation showed a positive but non-significant association (β = 0.181, p = 0.085), while gender was not significantly associated with perceived vulnerability. The model explained 92.8% of the variance in perceived vulnerability to illness (adjusted R² = 0.928). Perceived environmental health, mangrove-related knowledge, and formal education were significantly associated with perceived vulnerability to illness among coastal communities in mangrove ecosystems. These findings highlight the potential importance of health and environmental literacy in shaping risk perceptions within coastal populations. Further studies with longitudinal designs are needed to clarify the causal relationships between these factors.